Genes IX - Lewin, Benjamin (Jones and Bartlett Publishers, 2008)
From renowned author Benjamin Lewin comes the newest edition of his classic text, Genes IX. For decades Lewin has provided the teaching community with the most cutting edge presentation of molecular biology and molecular genetics, covering gene structure, sequencing, organization, and expression. The new Ninth Edition boasts a fresh modern design and contemporary art program, as well as a new organization which allows students to focus more sharply on individual topics. Thoroughly updated throughout, including a new chapter on Epigenetic Effects, Genes IX proves to be the most current, comprehensive and student-friendly molecular biology text available!